2017
DOI: 10.1002/pip.2860
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the key parameters for predicting PV soiling losses

Abstract: One hundred and two environmental and meteorological parameters have been investigated and compared with the performance of 20 soiling stations installed in the USA, in order to determine their ability to predict the soiling losses occurring on PV systems. The results of this investigation showed that the annual average of the daily mean particulate matter values recorded by monitoring stations deployed near the PV systems are the best soiling predictors, with coefficients of determination (R 2 ) as high as 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 31 publications
1
78
1
Order By: Relevance
“…The soiling station data have been analyzed using the method described in Micheli and Muller . Soiling has been quantified using the soiling ratio (r s,i ), which is a metric expressing the ratio, in percentage, between the short‐circuit current of the soiled device and the short‐circuit current of the control device.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The soiling station data have been analyzed using the method described in Micheli and Muller . Soiling has been quantified using the soiling ratio (r s,i ), which is a metric expressing the ratio, in percentage, between the short‐circuit current of the soiled device and the short‐circuit current of the control device.…”
Section: Methodsmentioning
confidence: 99%
“…In the recent years, several studies have investigated the relations between soiling losses and environmental parameters. The analysis of data recorded by 20 soiling stations installed in the United States has shown that the average concentrations of particulate matter and the average length of the dry period at each sites were the best parameters to predict the average soiling occurring over the long periods of data collection . Recently, a study conducted on performance and environmental data collected in Doha, Qatar, has shown how the prediction of daily soiling losses relies on complex correlations among multiple variables .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations